The Path Ahead: Readings in Death and Dying - Despelder Lynne Ann (McGraw -Hill, 1995)
This anthology directs attention to the evolving understanding of death and dying in today’s multicultural environment. Authoritative voices of pioneers and path?nders in the ?eld of death studies are joined by insightful commentators from intersecting disciplines, bringing depth and range of coverage to current knowledge about death, dying, and bereavement. This approach encourages critical thinking and allows students to examine their own feelings and beliefs about the path ahead.